2016
DOI: 10.1152/ajpendo.00387.2015
|View full text |Cite
|
Sign up to set email alerts
|

AMPKγ3 is dispensable for skeletal muscle hypertrophy induced by functional overload

Abstract: Riedl I, Osler ME, Björnholm M, Egan B, Nader GA, Chibalin AV, Zierath JR. AMPK␥3 is dispensable for skeletal muscle hypertrophy induced by functional overload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 41 publications
6
16
1
Order By: Relevance
“…Although both groups had comparable height and lean mass in the upper extremities, the overweight subjects had ~10% greater lean mass in the lower extremities reflecting an increased mechanical loading due to their excessive body mass. Even though functional overloading has been associated with increased SLN expression in mice, no significant differences in vastus lateralis SLN protein expression were observed between the overweight and lean subjects. A potential explanation for this finding could be that much larger overloading may be required to increase SLN expression in humans.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although both groups had comparable height and lean mass in the upper extremities, the overweight subjects had ~10% greater lean mass in the lower extremities reflecting an increased mechanical loading due to their excessive body mass. Even though functional overloading has been associated with increased SLN expression in mice, no significant differences in vastus lateralis SLN protein expression were observed between the overweight and lean subjects. A potential explanation for this finding could be that much larger overloading may be required to increase SLN expression in humans.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with rodent data, here we have demonstrated that a short training program based on repeated high‐intensity exercise reduced the SLN protein levels in vastus lateralis despite eliciting much less total energy expenditure than the 4‐day walking intervention. A principal difference between prolonged walking and repeated 30‐second all‐out sprints is the marked metabolic disturbances evoked by the sprints, which cause substantial lactic acidosis, oxidative stress, and sarcoplasmic reticulum stress .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Western blot analysis was as described ( Riedl et al., 2016 ). Antibodies used are provided in Supplemental Experimental Procedures .…”
Section: Methodsmentioning
confidence: 99%